Pediatric foreign body aspiration: A nidus for Aspergillus colonization. Issue 6 (June 2015) - Mitchell, Candace A.; Kreiger, Portia; Goff, Christopher; Shah, Udayan K.
Abstract: We describe an immunocompetent child with bronchial fungus following foreign body aspiration. A two-year-old male presented with cough. Workup revealed air trapping and bronchoscopy showed aspirated foreign material in the right mainstem bronchus. Histopathology revealed fungal organisms suggestive of Aspergillus within an ulcer of the adjacent bronchial mucosa. Foreign body aspiration has been posited as a nidus for aspergilloma formation but is not yet described in the available English-language pediatric literature. Here, the foreign body provided a site for fungal growth in the bronchus of an otherwise healthy child. This case suggests that bronchial foreign body may pose risk of fungal colonization even in immunocompetent children.